THE VOICE OF MENTOR TEACHERS AND STUDENTS TOWARD PRE-SERVICE TEACHERS TEACHING COMPETENCIES - Donal, Andri; Rafli, Zainal; Iskandar, Ifan (JEE (Journal of English Education), 2022)
This research aims to investigate students’ perspectives towards pre-service teachers’ competencies in teaching during the teaching practice program and to investigate teachers’ perspectives towards pre-service teachers’ competencies in teaching during teaching. The type of this research is a descriptive quantitative ex post facto research design. The populations of this research are English teachers and Students of Senior high school who pre-service teachers taught. Eleven pre-service teachers teach in senior high schools in seven schools as the location of research. In taking the samples, researchers used total sampling for the teacher samples and purposive sampling technique for student samples by taking ten students from each pre-service teacher. The research result showed that students’ perspective toward pre-service teachers’ competency in teaching was excellent. It was also similar to the teachers’ perspective toward pre-service teachers’ competency in teaching. It means that the teaching practice program held by the University of Pasir Pengaraian, especially the English education study program, was successful.